Low moisture anhydrous ammonia pretreatment of four lignocellulosic materials—distillers dried grains with solubles, corn gluten feed, corn fiber, and oil palm frond - Nazira, Mahmud; Rosentrater, Kurt A. (Frontiers Media S.A., 2021)
Lignin and hemicellulose structures in cellulosic materials serve as a barrier for enzyme reactions. A pretreatment step is often needed to break these components to allow the biomass to be utilized as a source of value-added products. Various available pretreatment methods possess common drawbacks of the high amount of liquid and chemical requirements, harsh process conditions, and the high amount of waste produced, which driving up the production costs of bioproducts. Low moisture anhydrous ammonia (LMAA) pretreatment capable of eliminating those drawbacks. In this study, Distillers Dried Grains with Solubles (DDGS), corn gluten feed (CGF), corn fiber (CF), and oil palm frond (OPF) with different moisture contents were subjected to LMAA pretreatment at the specific ammonia loading rate, 1 h ammoniation, and 75°C incubation temperature. This pretreatment successfully decreased the lignin content of the materials, increased their percentage of α-cellulose, and improved enzymatic digestibility for most of the materials tested. The effect of moisture content (30 and 50% db) was found to be more significant than that of incubation time (24 and 72 h).